Estimation of Serum Levels of AST, LDH, CKMB AND TCK Among HIV Patients on HAART, HAART Naïve and Controls (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Human Immunodeficiency virus (HIV) infection is associated with increased of developing heart disease. Information on the cardiac status of HIV-infected Nigerians is lacking. HIV/AIDS infection is a global pandemic and poses a serious health challenge in sub-Saharan Africa, Nigeria inclusive. The cardiac disease may occur at any stage of HIV infection, but important manifestations are more frequent with advanced immunodeficiency. Moreover, it has been reported that complications from HIV infection include arrhythmias, heart failure myocardial infarction and coronary heart disease. This study aimed to estimate serum levels of AST, LDH, CKMB and TCK among HIV patients on HAART, HAART naïve and controls subjects attending Bauchi State Tertiary hospital, Nigeria. The results showed that the mean serum total Creatine kinase, CK-MB, LDH and AST were significantly higher in  HIV participants not on HAART compared with HIV participants on HAART at P
Keywords: Serum; Enzymes; HIV; HAART; Naïve and Controls